Direct force control for human-machine system with friction compensation. Issue 5 (3rd May 2016) - Yu, Lie; Zheng, Jianbin; Wang, Yang; Zhan, Enqi; Song, Qiuzhi
Abstract : Purpose: – The purpose of this paper is to present a direct force control which uses two closed-loop controller for one-degree-of-freedom human-machine system to synchronize the human position and machine position, and minimize the human-machine force. In addition, the friction is compensated to promote the performance of the human-machine system. Design/methodology/approach: – The dynamic of the human-machine system is mathematically modeled. The control strategy is designed using two closed-loop controllers, including a PID controller and a PI controller. The frictions, which exist in the rotary joint and the hydraulic wall, are compensated separately using the Friedland's observer and Dahl's observer. Findings: – When human-machine system moves at low velocity, there exists a significant amount of static friction that hinders the system movements. The simulation results show that the system gives a better performance in human-machine position synchronization and human-machine force minimization when the friction is compensated. Research limitations/implications: – The acquired results are based on simulation not experiment. Originality/value: – This paper is the first to apply the electrohydraulic servo systems to both actuate the human-machine system, and use the direct force control strategy consisting of two closed-loop controllers. It is also the first to compensate the friction both in the robot joint and hydraulic wall.